2019
DOI: 10.1101/734640
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Superfast periodicities in distress vocalizations emitted by bats

Abstract: spectrum Abbreviations:AM: amplitude modulation, d: Cliff's delta, DPOAE; distortion product otoacoustic emissions, FFR: frequency following response, FOI, frequency of interest, FPV: fast periodic vocalizations, HND: harmonic-to-noise difference, HR: heart rate, iEEG: intracortical encephalogram, IQR; interquartile range, MPS: modulation power spectrum, qCF-FM: quasiconstant frequencyfrequency modulated, SFM: sinusoidal frequency modulation, SVM: support vector machine, TMS: temporal modulation spectrum. Abst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…For instance, mice could have been sensitive to the slope of the ramp in each sinusoidal cycle of AM sounds ( Deneux et al, 2016 ). However, in other mammals (otters, primates or bats), studies indicate that fast AM sounds, such as a baby’s cry, are also produced in alarm calls, and/or antagonistic interactions ( Leinonen et al, 2003 ; Mumm and Knörnschild, 2017 ; Hechavarría et al, 2019 ). Since infant distress calls appear to share acoustic similarities and analogous neuronal responses across mammals ( Newman, 2007 ; Zuberbühler, 2009 ; Lingle et al, 2012 ; Lingle and Riede, 2014 ), it is often suggested that rough sounds could elicit unpleasantness in many species as well.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, mice could have been sensitive to the slope of the ramp in each sinusoidal cycle of AM sounds ( Deneux et al, 2016 ). However, in other mammals (otters, primates or bats), studies indicate that fast AM sounds, such as a baby’s cry, are also produced in alarm calls, and/or antagonistic interactions ( Leinonen et al, 2003 ; Mumm and Knörnschild, 2017 ; Hechavarría et al, 2019 ). Since infant distress calls appear to share acoustic similarities and analogous neuronal responses across mammals ( Newman, 2007 ; Zuberbühler, 2009 ; Lingle et al, 2012 ; Lingle and Riede, 2014 ), it is often suggested that rough sounds could elicit unpleasantness in many species as well.…”
Section: Discussionmentioning
confidence: 99%
“…Individual C. perspicillata have distinctive vocal signatures. Distress calls have been shown to activate neurons in the amygdala (Hechavarría et al, 2020). Mapping gonadal steroid hormone receptor distributions in C. perspicillata will be a useful test of evolutionary hypotheses.…”
Section: Reproductive State: Comparing Cns Gonadal Hormone Receptor E...mentioning
confidence: 99%
“…Nevertheless, social vocalizations can be used in interspecific eavesdropping, e.g., distress calls may attract heterospecifics who approach the calls to investigate the situation by themselves (Carter et al, 2015) and thus increase the chance of repelling predators (Russ et al, 2004) or even deter predators directly (Ancillotto et al, 2022). This interspecific communication might be further facilitated, especially in the case of distress calls, by shared acoustic call features (Hechavarría et al, 2020). Several studies have directly compared the effect of conspecific and heterospecific social 10.3389/fevo.2022.950951 calls on bats, with the overall effect that heterospecific social calls elicit a weaker response, if any, than conspecific social calls (Fenton et al, 1976;Schöner et al, 2010;Furmankiewicz et al, 2011;Hörmann et al, 2021).…”
Section: Introductionmentioning
confidence: 99%